Trastuzumab inhibits pituitary tumor cell growth modulating the TGFB/SMAD2/3 pathway - Petiti, Juan Pablo (2018)
In pituitary adenomas, early recurrences and resistance to conventional pharmacotherapies are common, but the mechanisms involved are still not understood. The high expression of epidermal growth factor receptor 2 (HER2)/extracellular signal-regulated kinase (ERK1/2) signal observed in human pituitary adenomas, together with the low levels of the antimitogenic transforming growth factor beta receptor 2 (TBR2), encouraged us to evaluate the effect of the specific HER2 inhibition with trastuzumab on experimental pituitary tumor cell growth and its effect on the antiproliferative response to TGFB1. Trastuzumab decreased the pituitary tumor growth as well as the expression of ERK1/2 and the cell cycle regulators CCND1 and CDK4. The HER2/ERK1/2 pathway is an attractive therapeutic target, but its intricate relations with other signaling modulators still need to be unraveled. Thus, we investigated possible cross-talk with TGFB signaling, which has not yet been studied in pituitary tumors. In tumoral GH3 cells, co-incubation with trastuzumab and TGFB1 significantly decreased cell proliferation, an effect accompanied by a reduction in ERK1/2 phosphorylation, an increase of SMAD2/3 activation. In addition, through immunoprecipitation assays, a diminution of SMAD2/3-ERK1/2 and an increase SMAD2/3-TGFBR1 interactions were observed when cells were co-incubated with trastuzumab and TGFB1. These findings indicate that blocking HER2 by trastuzumab inhibited pituitary tumor growth and modulated HER2/ERK1/2 signaling and consequently the anti-mitogenic TGFB1/TBRs/SMADs cascade. The imbalance between HER2 and TGFBRs expression observed in human adenomas and the response to trastuzumab on experimental tumor growth may make the HER2/ERK1/2 pathway an attractive target for future pituitary adenoma therapy.